Urethral Squamous Cell Papilloma: A Rare Case Report and Review of the Literature - Serdar Çelik; Halil Hakan Özgür; Kutsal Yörükoğlu; Mehmet Uğur Mungan (Journal of Urological Surgery, 2018)
Urethral squamous cell papilloma is a benign lesion commonly presenting with lower urinary tract symptoms, such as dysuria and intermittent poor urinary flow. Surgical excision and careful pathological investigation are required for definite diagnosis and treatment. The probability of recurrence is fairly low. These lesions are generally observed in the urethra in post-menopausal women. This paper presents a case of squamous cell papilloma in the male anterior urethra in an 18-year-old male patient, who underwent surgical excision, and a literature review.